Strategic Choice and Operational Performance: A comparative study of commercial banks in Oman - Y. Sree Rama Murthy, James Rajasekar, (Opción)
The objective of this paper is to investigate various strategies adopted by banks in the Sultanate of Oman and to explore how these strategies may have helped these banks overcome different operational difficulties during periods of crisis. The empirical analysis in this study was done using binary logit regression technique with data from the Bank Scope database. Data was drawn from the balance sheets and income statements of commercial banks, and this data ranges from December 1999 to December 2017. Data from 1999 to 2009 was used for estimating the logit equations, and data from 2012 to 2017 was used for testing the predictive ability of the model. From a strategy point of view, our study of Omani banks focuses on the financial crises of 2000-2001 and 2008-2009, and the model predictions for years 2012 to 2017 brings forth the following conclusion: In order to ensure that a bank performs well (in terms of profit and asset growth), the bank’s management should focus on capital account management, interest spread management, good loan quality, and high loan-todeposit ratios. Finally, we also found that cost management and liquidity management are two areas of strategic choices that are not particularly important.